Teacher Agency: Bridging Gaps in Elementary Curriculum Implementation - Librando, Jade (Journal of Interdisciplinary Perspectives, 2025)
This comparative case study investigates the widespread challenge of curriculum implementation gaps in elementary education by examining teacher experiences across three distinct curricular approaches in the Philippines. The research addressed a critical gap in the literature by simultaneously analyzing foundational (Blocks of Time), revised (K-12), and pilot (MATATAG) curricula to identify systemic barriers and effective adaptive strategies. Utilizing in-depth thematic analysis of interviews with three public school teachers (representing Kindergarten, Grade 3, and Grade 4), the study provided a detailed, triangulated perspective across diverse contexts. Principal results consistently revealed a profound systemic misalignment—characterized by content overload, rigid pacing mandates that conflict with pedagogical goals, and widespread resource deficits. In response, the study determined that Teacher Professional Agency functions as an unrecognized operational safeguard, enabling continuity through strategic content prioritization and peer collaboration (Learning Action Cells). The major conclusion is that these implementation failures fundamentally undermine the success of policy. This necessitates an urgent policy shift that formalizes Teacher Agency as a core strategy for effective, localized curriculum delivery, moving beyond treating it as a simple coping mechanism.